Identification of a Five-Autophagy-Related-lncRNA Signature as a Novel Prognostic Biomarker for Hepatocellular Carcinoma - Deng, Xiaoyu; Bi, Qinghua; Chen, Shihan; Chen, Xianhua; Li, Shuhui; Zhong, Zhaoyang; Guo, Wei; Li, Xiaohui; Deng, Youcai; Yang, Yao (Frontiers in Molecular Biosciences, 2021)
Although great progresses have been made in the diagnosis and treatment of hepatocellular carcinoma (HCC), its prognostic marker remains controversial. In this current study, via weighted correlation network analysis (WGCNA) and Cox regression analysis on the database of HCC patients from The Cancer Genome Atlas (TCGA), we constructed a five autophagy-related long non-coding RNA (AR-lncRNA) prognostic signature for HCC. This signature includes TMCC1-AS1, PLBD1-AS1, MKLN1-AS, LINC01063, and CYTOR, all of which were highly expressed in the high-risk group of HCC patients. This five-AR-lncRNA prognostic signature showed good area under the curve (AUC) value (AUC = 0.751) for the overall survival (OS) prediction of all HCC patients. It also performed well in each stratified group of HCC patients classified by several clinical traits. We then used this five-AR-lncRNA prognostic signature to establish a good nomogram for the prediction of the 3- and 5-year OS outcomes of HCC patients intuitively (concordance index = 0.745). By parallel comparison, this five-AR-lncRNA signature has better prognosis accuracy than three recently published signatures. Furthermore, it also efficiently predicted the therapeutic outcomes of HCC patients, including chemotherapy and immunotherapeutic responses. Gene set enrichment analysis (GSEA) and gene mutation analysis revealed that dysregulated cell cycle pathway, purine metabolism and TP53 mutation may play an important role in determining the OS outcomes of HCC patients in the high-risk group. Collectively, our study suggests a new five-AR-lncRNA prognostic signature for HCC.